PROBLEMATIKA YANG DIHADAPI MAHASISWA CALON GURU FKIP UNIVERSITAS ABULYATAMA PADA PROGRAM PRAKTIK PENGALAMAN LAPANGAN - Hallaby, Syarifah Fadiya; Hamama, Syarifah Farissi (Jurnal Pendidikan Almuslim, 2018)
Difficulties encountered by student teacher during teacher training program were identified in this study. Descriptive method with questionaire as research instrument was used to gather information related to students difficulties. Forty eight respondents from Teaching Faculty of Abulyatama University were involved. The results revealed that lack of self confidence, class management, low level of competency in curriculum, teaching and learning method and also in assessing student work were the most difficulties often perceived by student teacher during teacher training program. Kata kunci        : difficulties, student teacher, teacher training program